Improving The Ability Of Back Kicks Through The Circuit Training Method For Tarung Derajat Athletes Kurata Second Degree In Siginjai Museum Training Unit - Sukendro Sukendro (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
This study aims to determine the improvement of back kick ability through the Circuit Training method in fighting athletes of Kurata second degree Tarung Derajat in Siginjai Museum training unit. The method used in this study is the Sports Action Research method which was conducted on 14 athletes, with the sampling technique based on CAR (classroom action research) in sports.The implementation of this research was carried out for 2 months with a frequency of training 3 times a week or 36 meetings. In the meeting, circuit training was given at each meeting to improve the ability of back kicks. Data analysis was carried out by means of data exposure and data reduction.Based on the table description of the results of the initial test of the first cycle of back kick ability, it can be seen that the kick ability of the athletes of Kurata second degree Tarung Derajat in the Siginjai museum training unit is still relatively low. It can be seen from the 14 athletes who were the subjects in this study, it turned out that only 9 athletes (64%) had complete results, while the remaining 5 athletes (36%) did not have complete training results than the expected 70% in cycle II action.In the results of the second cycle test, it can be seen an increase in back kick ability. It can be seen from the 14 athletes who were the research subjects that there were 13 athletes (98.2%) who achieved graduation. Meanwhile, only 1 athlete (7.1%). Judging from these results, it can be concluded that the Circuit Training method can improve the ability of back kicks in athletes of Kurata second degree Tarung Derajat in siginjai museum training unit.